TRP Channel Agonists Activate Different Afferent Neuromodulatory Mechanisms in Guinea Pig Urinary Bladder - Daugherty, Stephanie L.; Beckel, Jonathan M.; Kim, Kyoungeun A.; Freeman, Bruce A.; Liu, Jiaxin; Wang, Shaoyong; de Groat, William C.; Zhang, Xiulin (Frontiers in Physiology, 2021)
Activation of TRP channels expressed in urinary bladder afferent nerves and urothelium releases neurotransmitters that influence bladder function. Experiments were undertaken to examine the mechanisms underlying effects of TRPA1 (allyl isothiocyanate, AITC), TRPV1 (capsaicin, CAPS), and TRPC (oleoyl-2-acetyl-sn-glycerol, OAG) agonists on guinea pig bladder activity. Effects of these agonists were compared with effects of nitro-oleic acid (OA-NO2), an electrophilic nitro-fatty acid, known to activate TRPV1, TRPA1 or TRPC channels in sensory neurons. AITC (100 μM) increased (231%) area of spontaneous bladder contractions (SBCs) an effect reduced by a TRPA1 antagonist (HC3-03001, HC3, 10 μM) and reversed to inhibition by indomethacin (INDO, 500 nM) a cyclooxygenase inhibitor. The post-INDO inhibitory effect of AITC was mimicked (39% depression) by calcitonin gene-related peptide (CGRP, 100 nM) and blocked by a CGRP antagonist (BIBN, 25 μM). CAPS (1 μM) suppressed SBCs by 30% in 81% of strips, an effect blocked by a TRPV1 antagonist (diarylpiperazine, 1 μM) or BIBN. SBCs were suppressed by OA-NO2 (30 μM, 21% in 77% of strips) or by OAG (50 μM, 30%) an effect blocked by BIBN. OA-NO2 effects were not altered by HC3 or diarylpiperazine. OA-NO2 also induced excitation in 23% of bladder strips. These observations raise the possibility that guinea pig bladder is innervated by at least two types of afferent nerves: [1] Type A express TRPA1 receptors that induce the release of prostaglandins and excite the detrusor, [2] Type B express TRPV1, TRPA1 and TRPC receptors and release CGRP that inhibits the detrusor.